Driving Change Within Local Governments In The Netherlands: A Perspective On Administrative And Political Leadership - Rondeel, Patrick (My University, 2023)
This thesis explores the impact of political and administrative leadership on the digital transformation process within local government institutions in the Netherlands, employing a qualitative research approach through three in-depth case studies in the middle region of the country. I utilized a within-case and cross-case analysis methodology supplemented by validation interviews, conducting a total of 12 semi-structured interviews with key representatives from the selected institutions. The research uncovers the complex dynamics and tensions between political and administrative leadership and their consequential effect on digital transformation. I scrutinized critical factors such as power dynamics, role conflict, change management, leadership transition, interpersonal conflict, and stakeholder management. I found that these elements significantly influence organizational effectiveness and the resource-based view, a fundamental concept that local governments rely on for their digital transformation. The study's findings suggest that the interaction between political and administrative leadership significantly affects the direction, speed, and effectiveness of digital transformation initiatives in local government institutions. Furthermore, it demonstrates how intra-organizational dynamics and tensions, coupled with the existing political and administrative structure, can either facilitate or hinder digital transformation, thus offering vital insights for both theory and practice. These conclusions contribute to the growing body of literature in the fields of digital transformation, public administration, and political science, providing practical implications for local governments considering embarking or accelerating their digital transformation journeys. Furthermore, it underlines the importance of effective leadership and collaboration, enhancing the understanding of digital transformation in the context of public sector institutions and the inherent complexities therein.
Keywords: Leadership, Political, Administrative, Dynamics, Digital Transformation